Trade Integration and Export Aspiration: Evidence from India’s Trade in Goods with BRICS Countries - Ahad Bhat, Mudaser; Jamal, Aamir; Nazrana Beg, Mirza (Organizations and Markets in Emerging Economies, 2022)
The purpose of this study was to examine the dynamics of trade between India and the BRICS countries as well as to gauge the relative strength of Indian exports to those nations. The trade integration patterns among BRICS countries were also analyzed. To quantify the extent to which India’s exports correspond to the needs of its BRICS counterparts, a novel export aspiration index was constructed. The index of trade integration patterns has also been employed to quantify India’s trade integration pattern with other BRICS members. Further, the gravity model of trade has been employed to analyze the fundamentals of India–BRICS trade. The export aspiration in individual BRICS countries shows a diverse pattern. However, India’s export aspiration in these countries has improved, although marginally in the long run. Such empirical evidence substantiates that the relative strength of India’s exports within its BRICS counterparts has marginally improved over time. Moreover, the trade integration index indicates a similar trade integration pattern among the BRICS countries and corroborates the presence of inter-industry trade. Added to the conventional variables of the gravity model, India’s outward multilateral trade resistance and BRICS inward multilateral trade resistance significantly promote India–BRICS trade. Hence, the relative strength of Indian exports will increase substantially if India’s commodity composition is diversified by including more commodities in its export baskets that correspond to the needs and changing conditions of the BRICS economies.
Keywords: India-BRICS Trade; Export Aspiration; Gravity Model; Multilateral Trade Resistance